On the correct identification of ‘Cyana dohertyi (Elwes, 1890)’ from northern Indochina and China, with descriptions of two new species and a new subspecies (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Saldaitis, Aidas; Ivanova, Maria S. (Zootaxa, 2019)
Two new species similar to Cyana dohertyi (Elwes, 1890), C. lada Volynkin, Černý & Saldaitis, sp. nov. (Vietnam and China) and C. titovi Volynkin, Černý & Ivanova, sp. nov. (Vietnam) are described. A new subspecies C. dohertyi mertsana Volynkin & Černý, ssp. nov. is described from North Thailand and North Vietnam. Adults, male and female genitalia of the new and related species are illustrated.